Katalog vpijatov (Coraciiformes) ornitološke zbirke Prirodoslovnega muzeja Slovenije - Vrezec, Al (Scopolia, 2017)
The catalogue presents the data on all specimens of Coraciiformes in the collection of the Slovenian Museum of Natural History (PMS). These are preserved specimens from inventory books, specimens recorded in accession books and fieldnotes, as well as data on lost specimens. The main source of information is the old inventory book named as the Inventory book of mammals, fish, birds, reptiles of the Natural History Museum. Most of the data on study skins are from the Catalogue of bird collection of the State Ornithological Observatory. The specimens obtained during the expedition to Ethiopia are recorded in the Field Book of Savo Brelih. All preserved specimens are now recorded in the Inventory book for birds of the Slovenian Museum of Natural History in the Galis system or in the Accession book for birds of the Slovenian Museum of Natural History. Altogether, 124 specimens of 15 Coraciiformes species were recorded by 2016. The first specimens were acquired by taxidermist Ferdinand Schulz in 1873. A larger number of specimens were received by the Museum between 1890 and 1897. Another major accession was the expedition by Savo Brelih into Ethiopia between 1960 and 1961. After 1980, the number of acquisitions increased with the salvage of dead birds. Best represented Coraciiformes in the PMS collection are species occurring in Slovenia, i.e. the European Roller (Coracias garrulus), the Common Kingfisher (Alcedo atthis) and the European Bee-eater (Merops apiaster). The remaining material originates from seven countries of Europe, Africa and North America. By 2016, only about half of all collected specimens were preserved in the ornithological collection. The preserved specimens constitute only 1% of the entire PMS ornithological collection, but the share of lost museum specimens exceeds the share of lost specimens in other natural history museums in Europe.
Keywords: accession; akcesija; Alcedinidae; bird collectors; birds; collection history; Coraciidae; Coraciiformes; inventar; inventory; Meropidae; museum collections; muzejske zbirke; ornitologija; Prirodoslovni muzej Slovenije; Ptiči; Slovenia; Slovenian Museum of Natural History; Slovenija; vpijati; zbiralci ptic